2023
DOI: 10.3389/fimmu.2023.1121973
|View full text |Cite
|
Sign up to set email alerts
|

PRAME and CTCFL-reactive TCRs for the treatment of ovarian cancer

Abstract: Recurrent disease emerges in the majority of patients with ovarian cancer (OVCA). Adoptive T-cell therapies with T-cell receptors (TCRs) targeting tumor-associated antigens (TAAs) are considered promising solutions for less-immunogenic ‘cold’ ovarian tumors. In order to treat a broader patient population, more TCRs targeting peptides derived from different TAAs binding in various HLA class I molecules are essential. By performing a differential gene expression analysis using mRNA-seq datasets, PRAME, CTCFL and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“… 64 Rosenberg et al 57 , 112 used TCR‐T targeting MAGE‐A3 to treat a variety of advanced metastatic solid tumors and achieved positive clinical efficacy; they confirmed the efficacy of MHCII‐TCR CD4 T cell therapy targeting MAGE‐A3 and expanded the therapeutic range of TCR‐T for metastatic tumors. Amerongen 72 and colleagues found that the PRAME and CTCFL TCR‐T cells demonstrated potent and specific antitumor reactivity both in vitro and in vivo, the identified PRAME and CTCFL TCRs are promising candidates for the treatment of patients with ovarian cancer. Novel TCR optimization strategies for multiple tumor antigens have been proposed.…”
Section: Application Prospect Of Cta In Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“… 64 Rosenberg et al 57 , 112 used TCR‐T targeting MAGE‐A3 to treat a variety of advanced metastatic solid tumors and achieved positive clinical efficacy; they confirmed the efficacy of MHCII‐TCR CD4 T cell therapy targeting MAGE‐A3 and expanded the therapeutic range of TCR‐T for metastatic tumors. Amerongen 72 and colleagues found that the PRAME and CTCFL TCR‐T cells demonstrated potent and specific antitumor reactivity both in vitro and in vivo, the identified PRAME and CTCFL TCRs are promising candidates for the treatment of patients with ovarian cancer. Novel TCR optimization strategies for multiple tumor antigens have been proposed.…”
Section: Application Prospect Of Cta In Ovarian Cancermentioning
confidence: 99%
“…Similarly, the CTCFL TCR‐T cells efficiently recognized ovarian cancer cell lines treated with DAC, implying that pretreatment with DAC may increase the reactivity of transferred TCR‐T cells in patients. 72 Epigenetic regulation not only affects tumor cells but also affects the immune cells of the body. HDAC inhibitors have immune stimulatory effects, and the host immune system also plays an important role in mediating the sustained antitumor response of HDAC inhibitors.…”
Section: Application Prospect Of Cta In Ovarian Cancermentioning
confidence: 99%
“…Specific TCRs were isolated from allogeneic HLA donors, and TCR-T cell therapy targeting CTCFL has been developed. These TCRs could recognize tumor cells from ovarian cancer patients [54] . The immunoglobulin J chain is overexpressed in multiple myeloma, and TCRs targeting HLA-A*01, A*24, A*03, or A*11-restricted J chain peptides have been discovered.…”
Section: Tumor Antigensmentioning
confidence: 99%
“…Immune checkpoint inhibitors enhance the anti-cancer effect of treatment, thereby blocking the progression of tumors ( 22 ), especially in melanoma, lung cancer, and kidney cancer ( 23 25 ). However, the treatment is not effective against all tumor types (e.g., ovarian cancer, prostate cancer, pancreatic cancer, and glioblastoma) because certain tumors are “cold” due to the inability of immune cells to identify cancer cells ( 26 , 27 ). This limits the effectiveness of immune checkpoint inhibitors, thus resulting in poor immune therapy outcomes ( 28 , 29 ).…”
Section: Introductionmentioning
confidence: 99%